Property Company Condition in IKN Phenomenon Using Bankruptcy Models - Teofilus Karnalim; I Gusti Ngurah Agung Arya Bhakta Narayana; Christoffel Jehezkiel Gracesttela; Eriko Sucipto; Jessica Lie (Penerbit Goodwood, 2025)
Purpose: Amid the significant shift of the capital city relocation to IKN, it is essential to determine whether property companies are navigating within a zone of financial distress or maintaining a position of financial stability and safety. Methodology/approach: The researcher uses the Altman Z-Score, Springate, Ohlson, and Zmijewski models to determine the condition of property companies, whether they are in the distress zone or the safe zone. Results/findings: This study shows that in 2019 - 2023 there are 3 company on distress zone, 4 company on gray zone, 68 company on Safe zone using Altman Z-Score, for Springate there are 49 in distress zone and 22 in safe zone, for Ohlson 28 in distress zone and 47 in safe zone, for Zmijewski there are 1 in Distress Zone and 74 in safe zone. Conclusion: The study finds that most companies are classified as financially safe by the Altman and Zmijewski models, while the Springate and Ohlson models identify more companies in distress, especially during 2020–2021. Limitations: This study is limited to property companies, and only the condition is considered. The accuracy of the four bankruptcy models, namely, the Altman Z-score, Springate, Ohlson, and Zmijewski models, is not measured. Contribution: This study contributes to those who need to see the company property condition, whether the company is in financial distress or not. It is hoped that this study will help others, whether researchers or civilians, to understand the condition of property companies.